Pengembangan Motif Berbasis Digital pada Usaha Tenun Kubang H.Ridwan By di Kabupaten Lima Puluh Kota - Ratni Prima Lita; Meuthia Meuthia; Sari Surya (Yayasan Riset dan Pengembangan Intelektual, 2020)
Tenun Kubang H.Ridwan By, which is located in 50 Kota Regency, continues to strive the increasing of its product's attractiveness through unique motifs and retain the characteristic of Minangkabau motifs. Motifs designed manually take a long time and craftsmen have difficulty designing more varied motifs. Therefore, craftsmen are trained to design motifs using digital technology. The method used in the activity are training and practice methods. The first step is the craftsman was taught the basics of designing digitally, then was given the task to do it. The second step is the craftsmen are given training on advanced designs with a more difficult level and practice it into motif designs such as roses, kaluak paku and others. The third step is that the craftsmen begin to practice the motifs in the weaving process and produce more attractive and custom-made woven products. The results obtained, the craftsmen work on a motif design faster, attractive, as well as mix and match colors more attractive. It has an impact on the speed of production and produce the products that have a better appeal to consumers. Keywords: Motif, Digital, Production